APAKAH MUTU LAYANAN AKADEMIK MEMENGARUHI KEPUASAN MAHASISWA FMIPA UNUD BELAJAR DI MASA PANDEMI - RIFAI, MUHAMAD; KENCANA, I PUTU EKA NILA; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Vol 11 No 2 (2022), 2022)
Colleges as service providers must provide satisfaction to their students. At the concept of service, students as a group of consumers should get optimum service. The aim of this research is to determine the effect of the quality of academic services on student satisfaction at the Faculty of Mathematics and Natural Sciences, Udayana University during the Covid-19 pandemic. The analysis technique uses Partial Least Square Structural Equation Modeling (PLS-SEM). The results show that the dimensions of tangibles and empathy are proven to be significant, while dimensions of reliability, responsiveness, and assurance is not proven to significantly affect the quality of academic services. Increased the quality of academic services has proven to have a positive and significant effect on student satisfaction of FMIPA UNUD.